Disciplines, Demographics, & Expertise: Foundations for Transferring Professional Norms in Nonprofit Graduate Education. (4th March 2023) - Evans, Michelle D.; Irizarry, Jose Luis; Freeman, J. Kenzie
Abstract: Every profession has a common core of values and professional norms that help legitimize expertise and standardize behavior, which are both molded by and instilled through socialization and teaching in educational programs. Accreditation and professional associations help influence the transfer of these norms, including attention to not just what we are teaching, but also how we are teaching it, and what underlying messages we are communicating. We broaden that to also examine who is teaching by examining demographics, expertise, and disciplinary influences as a notable influence on the socialization process of professional norms and values. Our findings show that nonprofit graduate programs represent three main disciplinary influences. The professional expertise of faculty is even more wide-ranging and women account for a higher percentage of instructors than public administration degrees or across all academic disciplines. Efforts to infuse professional norms in nonprofit studies may be complicated by the lack of disciplinary home for the field and a corresponding variety of disciplinary backgrounds for assigned professors.